Tandem mass spectrometry determined maternal cortisone to cortisol ratio and psychiatric morbidity during pregnancy−interaction with birth weight. (July 2016) - Hellgren, Charlotte; Edvinsson, Åsa; Olivier, Jocelien D.; Fornes, Romina; Stener-Victorin, Elisabet; Ubhayasekera, S.J. Kumari A.; Skalkidou, Alkistis; Bergquist, Jonas; Sundström-Poromaa, Inger
Graphical abstract: Highlights: Maternal serum cortisone and cortisol did not differ with psychiatric morbidity. No group differences in cortisone ratio or placental dehydrogenase mRNA levels. Cortisone ratio was positively associated to birth weight in psychiatric morbidity. Psychiatric morbidity mayincreasefetal exposure to factors influencing growth. Abstract: Maternal serum cortisol has been suggested to be influenced by psychiatric morbidity, and may also influence fetal growth. However, several studies found equal cortisol levels in depressed and healthy pregnant women. Placental 11-β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) shields the fetus from maternal cortisol by conversion to cortisone, a function that may be compromised by maternal stress. We aimed to compare the serum ratio of cortisone to cortisol, in women with and without psychiatric morbidity during pregnancy. A secondary aim was to investigate whether fetal growth, approximated by infant birth weight, was associated with the cortisone to cortisol ratio. We performed tandem mass spectrometry analysis of serum cortisol and cortisone in late pregnancy in 94 women with antenatal psychiatric morbidity and 122 controls (cohort 1). We also compared the placental gene expression of HSD11B1 and 2 in another group of 69 women with psychiatric morbidity and 47 controls (cohort 2). There were no group differences in cortisol to cortisone ratio, absolute levels of cortisone and cortisol (cohort 1), or expression of HSD11B1 or 2 (cohort 2). However, cortisone to cortisol ratio was positively associated with birth weight in women with psychiatric morbidity, also after adjustment for gestational length, fetal sex, maternal height, smoking, SSRI use, and time of blood sampling (standardized β = 0.35, p < 0.001), with no association in the healthy controls Thus, the maternal serum cortisone to cortisol ratio does not seem to be affected by psychiatric morbidity, but psychiatric morbidity may increase fetal exposure to cortisol or other metabolic factors influencing fetal growth.